Nanofikasi Fraksi Tanah Gambut untuk Modifikator Nanomagnetit/AH-Kitosan sebagai Kandidat Penanggulangan Pencemaran Zat Warna - Ngatijo Ngatijo; Restina Bemis; Mahya Ihsan; Nurul Gusmaini; Salim Hidayat; Rahmat Basuki (CHEMPUBLISH JOURNAL, 2020)
The nanomagnetite/HA-Chitosan adsorbent has been successfully synthesized by the co-precipitation method. HA was synthesized from the peat soils of Geragai village, Tanjung Jabung Timur, Jambi province and chitosan isolated from marine animal shell waste around the city of Jambi. The results of FT-IR analysis showed that nanomagnetite/AH-chitosan has a spectra which was combination of the characteristic spectra of magnetite, HA and chitosan. Morphological analysis using SEM showed that nanomagnetite/AH-chitosan was in the form of fractal agglomerates. TEM image of magnetite/AH-chitosan showed that magnetite/AH-chitosan has nano scale magnetite core particles with a size between 4-22 nm. Crystallinity analysis showed that magnetite/AH-chitosan has 2θ characteristics of magnetite i.e., 30.1°, 35.4°, 43.1°, 57.0°, 62.68° and 74.5°. The magnetic saturation strength (Ms) decreased from 80.23 (magnetite) to 30.63 (magnetite/AH-chitosan) due to the coating of AH-chitosan on magnetite which was still effectively attracted by the external magnet with 96% effectiveness of adsorption of 25 mL Methylene Blue 10 mg/L.